2009
DOI: 10.1136/thx.2008.107821
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil TLR4 expression is reduced in the airways of infants with severe bronchiolitis

Abstract: Background:In respiratory syncytial virus (RSV) bronchiolitis, neutrophils account for >80% of cells recovered from the airways in bronchoalveolar lavage (BAL) fluid. This study investigated neutrophil activation and Toll-like receptor (TLR) expression in the blood and lungs of infants with severe RSV bronchiolitis.Methods:BAL fluid and (blood) samples were collected from 24 (16) preterm and 23 (15) term infants ventilated with RSV bronchiolitis, and 12 (8) control infants. Protein levels and mRNA expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 37 publications
(58 reference statements)
3
34
1
Order By: Relevance
“…Human studies also indicate an important role for neutrophils, linking neutrophils with impaired TLR4 signaling to severe RSV bronchiolitis (31). In the present studies we found that BPZE1 inoculation resulted in a very moderate neutrophil recruitment (,12% of BAL cells), and BPZE1 colonization caused no lung inflammation or neutrophil excess by Day 7 after infection, suggesting that BPZE1-mediated recruitment of neutrophils does not contribute to airway inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…Human studies also indicate an important role for neutrophils, linking neutrophils with impaired TLR4 signaling to severe RSV bronchiolitis (31). In the present studies we found that BPZE1 inoculation resulted in a very moderate neutrophil recruitment (,12% of BAL cells), and BPZE1 colonization caused no lung inflammation or neutrophil excess by Day 7 after infection, suggesting that BPZE1-mediated recruitment of neutrophils does not contribute to airway inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…For instance, it has been described that expression of TLR4 is significantly increased in epithelial cells after RSV challenge and during the inflammatory response induced by the virus [30]. Consistent with this observation, neutrophils recovered from bronchoalveolar lavages of RSV-infected preterm infants expressed significantly higher levels of TLR4 than did healthy infants, suggesting an increased inflammatory potential in those patients [31]. Furthermore, a recent study has also shown that RSVinfected human bronchial epithelial cells secrete the heat shock protein HSP72, which binds to TLR4 on neutrophils and leads to an increase on IL-8 and TNF-␣ production [32].…”
Section: Detection Of Rsv By Pattern Recognition Receptorssupporting
confidence: 77%
“…In severe RSV bronchiolitis it has been shown that the virus undergoes transcription in blood neutrophils (41), and that neutrophil TLR4 expression and function is reduced in the blood and airways (42), with distinct blood neutrophil subsets in severe viral infection (43). Interestingly, in our study gene expression of several granzymes and antimicrobial peptides (CAMP and DEFA1) associated with neutrophils were clustered with type-I IFNs, but were not significantly differentially expressed between severity groups.…”
Section: Discussionmentioning
confidence: 65%